Escrituras do candomblé: articulações entre o simbólico e o imaginário na cultura religiosa afro-brasileira - Barbosa, Jackson Cícero França (2022)
Since the colonial diaspora, the universe of black religion has always been of great interest. Nowadays, although in a timid way in relation to scientific research and observation devices, such disquiet is still present, not only because of the magical (hermetic) aspects conferred on such a religious system, but above all, because of the range of signs/symbols that compose the ritualistic language of Candomblé in Brazil. The semiotic universe of the religion of the orixás is composed of elements that structure a multifaceted language and, based on this, we question how candomblé is articulated as scripture (socio-historical and cultural process of production of meanings), through basic language elements for the manifestation of its rites? From categories that bring together symbolic elements that make up the writing of African-based religion and that are at the service of our investigation (artisanal, pictorial, performative), we believe that, even without the presence of traditional writing, of Western molds, these form a symbolic/signatory chain exercising the ontological functions of written systems that go beyond generations, establishing themselves as discourses: letter and voice (ZUMTHOR, 1993); referring elements as scriptures of a culture. In this sense, this thesis aims to highlight and categorize the forms that compose the candomblé scriptures, based on the language practices that are dynamized, in this religious system, through memory objects and the constitution of the mythical-symbolic imaginary (CASIRRER, 1972, 2001; ELIADE, 1991; 2016; DURAND, 2012) of the daily life of the circumscribed religion. It is a participant-research that, through ethnographic-based referrals, collects the signs/symbols that go back to narratives and discourses of the Afro-Brazilian religious system, corroborating a multifaceted perspective of writing that transcends the levels of inscription that are updated. within the various expressions of language within the scope of popular cultures. In the collection and examination of multifaceted memory objects that participate in the semiotic constitution of the symbolic writings of Candomblé, we also rely on Chevalier and Gheerbrant (1990) and on Jung (2000), in the defense that from our language ( verifiable in all cultures), in our gestures, our dreams, we use signs/symbols that give shape to desires, incite undertakings, shape behaviors, because we live in a world that is organized and makes sense through symbols, rites and fantastic, mythical and mystics. The embodiment of ritualized voices in the performance, as well as the constitution and unfolding of orality in the various writings, is established through the relationship between mythical-symbolic figures, images and objects of memory that are articulated as an extension of the body that emanates voices and images, corroborating the notion of writing that is established through an anthropological semiotic path (RODRIGUES, 2011) and, with that, the images-symbols of the religious system in vogue are boosted by the inscription of gestures, making a notion of writing be systematized. Thus, the body, as a support for the forms of inscription, in this context, is the locus sacer of these symbolic objects, pictorial, artisanal and imagetic-performatic writings of Candomblé.